Implementation of Goods and Service Tax (GST) in India and its Control over the Tax Collection - Debnath, Pranesh (Journal of Commerce and Trade, 2016)
Goods and Service Tax (GST) is a destination base indirect tax collected by central as well as state government to meet the public expenditure as a part of important mechanism of fiscal system of a nation. Unlike other prevailing indirect taxes Goods and Services Tax and is proposed to be a comprehensive indirect tax levy on manufacture, sale and consumption of goods as well as services with a input tax credit facility on output tax liability at the national and state level in an uniform modus. In this study an attempt has been made to draw the road map in connection with levy and collection of GST and its sharing between centre and state. Hence, GST is expected to unite the country economically as it will subsume various forms of taxes that are currently levied at different points subsuming the multiple types of taxes charged at different rate at present.